STUDY OF 3D PRINTING MODEL IN DENTAL HEALTH EDUCATION PRECLINIC PRACTICES: NARRATIVE REVIEW - Ni Nyoman Kasihani; Rikawarastuti Rikawarastuti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Preclinical learning is a basic exercise to develop skills, based on real cases in the laboratory before taking direct action on patients. However, many students feel stressed, lack confidence, and are not ready to perform dental treatment for patients for the first time. It is necessary to study learning media that are more realistic, and innovative by utilizing technology to bring closer to the real situation of dental treatment patients for students in preclinical. The purpose of this study was to identify the scope of use and benefits of 3D printing in preclinical learning in dental health education or dentistry. The research method is a narrative review using the keywords 3D printing, AND preclinical dental education on Google Scholar, ScienceDirect, and Pubmed search engines. The results of the study found 14 articles that met the criteria. 3D printing models have been used for endodontic preclinical practice, oral surgery, cavity preparation, management of dental trauma, tooth morphology, assessment of developmental instruments, and combined use with Virtual Reality. The benefits of 3D printing are that it can improve practical learning outcomes, the media is more realistic, and relevant for practice, increases self-confidence, reduces stress and students feel better prepared to care for patients. In conclusion, the use of 3D printing in preclinical practice includes complex dental practice simulations and the development of preclinical practice evaluation instruments that have been combined with other technologies. 3D printing is useful for improving practical learning outcomes, more realistic and relevant as a practicing medium, increasing self-confidence, reducing stress, and increasing students' readiness to perform dental treatment on patients.